The Influence of Organizational Culture and Self Efficacy on the Ability of Cadets Conflict Management in Lemdiklat Akpol Semarang - Tri Widada (Universitas Negeri Semarang, 2023)
The conflict management skills of cadets in the Education and Training Institute at the Semarang Police Academy (Akpol) are still low or not optimal. This needs special attention from all parties involved in the Akpol institution. Because of the various reasons put forward by cadets that they have not optimally practiced conflict management courses and that is only theoretical that cadets get. Therefore, it is necessary to pay attention to improving the ability of educators in teaching each material taught to cadets. This research is a quantitative study with a sample of 28 people. The data collection technique was a closed questionnaire technique while the data analysis technique used SPSS 21 to determine the influence of organizational culture, self-efficacy on the ability of cadets' conflict management at the Police Academy. The results showed that there was an influence of organizational culture by 28.1%, self-efficacy on conflict management by 49.5%. This shows that conflict management abilities can incre